MOTIF PENGGUNA MEDIA SOSIAL DALAM MENGUNGGAH INSTAGRAM STORY (Studi Fenomenologi Pada Anggota Sanggar Arastra di Kota Bengkulu) - Yurindah Yurindah; Sri Narti; Indria Indria (UNIVED PRESS, Universitas Dehasen Bengkulu, 2019)
Instagram social media is a unique medium because through this media not only communicating by sharing photos, but also penetrating into videos that everyone can get various videos that inform various kinds of actifities or routines that are carried out. The use of instagram also occurs among the community in the city of Bengkulu, precisely Sanggar Arastra community, thus encouraging members to play Instagram. The purpose of this study is to find out the motives of social media users to upload instagram story. This study uses a qualitative research method with a qualitative descriptive approach and this study uses the motive theory by Papacharissi and Rubin (2017), which consist of several motives, utility motives and motives seeking information. This research was conducted with data collection techniques through interview, observation and documentation study. The subjects in this study were five members of Sanggar Arastra owning an Android or iOS cellphone with an application and an Instagram account, they actively play Instagram and like ti upload photos, videoa and texts on the Instagram Story. The results of thie study indicate that the motives of members of Sanggar Arastra in uploading photos, videos nd texts in Instagram story are convenience motives, entertainment motives, passing time motives to follow current trends. Of all the motives, there is the most dominant motive, namely Convenience Motives because what they upload on Instagram stories is a form of expressing themselves, a place to express feelings in the form of photos, videoa and texts. Their uploads form a good image in order to get the desired recognition.